Optimization-Based Matching Layer Design for Broadband Dielectric Lens Antennas - Tokan, F. (APPLIED COMPUTATIONAL ELECTROMAGNETICS SOC, 2014)
Dielectric lens antennas fabricated with a dense dielectric material, allow good power transfer efficiency through the lens and enable fabrication of low-cost and compact-size lens antennas. On the contrary, using dense dielectric material causes strong multiple internal reflection behavior inside the lens antenna. These multiple reflections deteriorate not only return loss but also the radiation characteristics. However, the undesirable effects of strong internal reflections can be reduced considerably using one or more dielectric Matching Layers (MLs) coated at the top of the antenna. In this paper, a novel optimization-based ML design procedure for dielectric lens antennas is proposed. In order to demonstrate effectiveness of the method, the optimization procedure is applied to two different dielectric lens antennas; a narrow band lens antenna and an Ultra-Wideband (UWB) lens antenna. The simulation results verify that MLs designed by the proposed optimization procedure prevent strong internal reflections successfully for both narrow-band and UWB applications.
Keywords: Air-gap; dielectric lens antennas; matching layer; optimization; UWB antennas; NON DISPERSIVE RADIATION; INTERNAL REFLECTIONS; AUTOMOTIVE RADARS; SILICON; UWB; Engineering; Telecommunications